Mesenchymal Stem Cells Ameliorate Hyperglycemia in Type I Diabetic Developing Male Rats - Hany N. Yousef; Samia M. Sakr; Sahar A. Sabry (Stem Cells International)
One of the most promising treatments for diabetes mellitus (DM) is stem cell therapy. This study is aimed at elucidating the antidiabetic effect of mesenchymal stem cells (MSCs) on streptozotocin- (STZ-) induced DM in developing male rats. Twenty-four male albino rats (4 weeks old) were divided into control, diabetic, diabetic+MSCs1 (received MSCs one week after STZ treatment), and diabetic+MSCs2 (received MSCs 4 weeks after STZ treatment). Diabetic rats showed marked impairment (p<0.05) in serum levels of glucose, insulin, C-peptide, glycosylated hemoglobin (HbA1c), malondialdehyde (MDA), total antioxidant status (TAS), and total oxidant status (TOS) in addition to disruption of the calculated values of homeostatic model assessment of insulin resistance (HOMA-IR), pancreatic β cell function (HOMA-β), and oxidative stress index (OSI). These biochemical alterations were confirmed by the histopathological and ultrastructural assessments which showed marked destructive effect on pancreatic islet cells. MSC therapy in an early stage reversed most of the biochemical, histological, and ultrastructural alterations in the STZ-induced diabetic model and restored the normal cellular population of most acinar cells and islet of Langerhans. These results indicate that MSC therapy of STZ-induced diabetic developing rats during an early stage has the capacity of β cell restoration and the control of blood glycemic homeostasis.